Reconstruction Of Notary Position Authority and Implementation Of Basic Concepts Of Cyber Notary - Masrur Ridwan (Jurnal Akta, 2020)
E-notary or cyber notary which has become a necessity as a form of adjustment to the development of the times, although its presence is agreed to be impossible to avoid, but it still leaves a pro-cons opinion. Some support and some refuse. Problems that arise related to the validity of the deed made in the cyber notary work system (cyber notary). However the practice of cyber notary in Indonesia today, it will reduce the strength of proof of authentic deed. The decrease is parallel with the text of Article 5 paragraph (4) of the ITE Law which emphasizes that the electronic deed does not have perfect proof of strength like a deed of qualification. Until now the electronic deed is still regarded as a deed under the hand that is equal in value to documents. But the presence of COVID-19, which since March 11, 2020, was determined by WHO as a pandemic, like it or not, forced us to think or review the implementation of the basic concepts of cyber notary. Posts that use the statute approach and the concept are expected to be able to encourage related parties to review the authority of the Notary Position in authorizing the certification of transactions conducted electronically. Keywords: Reconstruction, Notary Authority, Implementation, Basic Concepts of Cyber Notary